Shared prognostic information in amyotrophic lateral sclerosis – systematic assessment of the patients’ perception of neurofilament light chain and the ALS functional rating scale - Lukas Maximilian Möhwald; André Maier; Torsten Grehl; Ute Weyen; Patrick Weydt; René Günther; Paul Lingor; Bettina Göricke; Susanne Petri; Julian Grosskreutz; Matthias Boentert; Isabell Cordts; et al. (Neurological Research and Practice)
Abstract Background In amyotrophic lateral sclerosis (ALS), neurofilament light chain (NfL) was introduced as a prognostic biomarker. More recently, NfL values can be shared on the patient’s ALS app. Also, the ALS functional rating scale (ALSFRS-R) is an established patient-reported assessment of disease progression. The scale can be obtained during clinic visits or remotely. However, few systematic data are available on the patients’ perception of prognostic information about NfL and ALSFRS-R and the remote sharing of these data. Methods In a multicenter study, 149 ALS patients were assessed for their perception of shared information about NfL and ALSFRS-R using an investigator-designed survey and established questionnaires. The recommendation of NfL and ALSFRS-R to fellow patients was assessed using the Net Promoter Score (NPS). Burden by shared information was investigated in two distinct settings: (1) clinic information when receiving results on NfL and/or ALSFRS-R during clinic visits and (2) remote information about NfL values and self-rating of the ALSFRS-R via the ALS app. General anxiety was measured by the Fear of Progression Questionnaire – Short Form (FoP-Q-SF). Results Information about NfL and ALSFRS-R, respectively (n = 149), were regarded as relevant for patients themselves (75.2% and 77.2%) and for research (98% and 96%). The NPS showed a high recommendation rate for NfL (+ 21) and ALSFRS-R (+ 26). Only a minority of patients perceived shared information about NfL as burdensome, with a lower burden in the clinic setting (n = 1, 4.2%) than in the remote setting (n = 8, 12%; p = 0.015). Remote digital assessment of the ALSFRS-R was well received, with a reported burden in 9.8% (n = 9) of the participants. The FoP-Q-SF revealed fear of progression in 40% of the respondents (n = 60). Conclusions This study underscored the relevance of information about NfL and ALSFRS-R from the patient’s perspective. Furthermore, patients proved to appreciate the relevance of this data for ALS research. Sharing information about NfL or ALSFRS-R was rarely perceived as burdensome even in a remote setting using the ALS app. These findings pave the way for further development of the patient-centered approach to sharing prognostic information in ALS.